Evaluation of Oxidative Stress After Exposure to Different Doses of Deltamethrin and Cadmium in Swordtail Fish Gills - (:unkn) unknown (ZOOLOGICAL SOC PAKISTAN, 2014)
In the present study, deltamethrin, a pyrethroid insecticide, and cadmium were investigated for their potency to induce oxidative stress. and effects on antioxidant systems in gill tissue of Swordtail fish (Xiphophorus hellerii). Animals were exposed to sublethal doses, of deltamethrin and cadmium for 72 hours except the control group. Protein, malondialdehyde (MDA), reduced glutathione (GSH) levels. and catalase (CAT) enzyme activities were determined. The results showed that total proteins MDA and GSH increased in each group, except for 0.2 ppm deltamethrin MDA and 0.1 ppm cadmium group where GSH was decreased. Catalase activity was decreased in all groups when compared to control group.
Keywords: Cadmium; deltamethrin; oxidative stress; swordtail fish; Xiphophorus hellerii; FRESH-WATER FISH; LIPID-PEROXIDATION; METAL ACCUMULATION; LIVER; PESTICIDES; BIOMARKERS; ENZYMES; TISSUES